Implementation of the Exo Olo Task Learning Model Integrated Case Method to Improve Students' High Order Thinking Skills (Hots) - rahman, andika; Nofrion, Nofrion (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
This article was written to describe the results of the Application of the EXO OLO Task Learning Model integrated Case Method to improve students' higher-order thinking skills on the distribution of flora and fauna in Indonesia and the world. The research method used is quasi-experimental. The subjects of the study were students of class XI IIS 2 of As-Shofa Islamic High School Pekanbaru as an experimental class and class XI IIS 1 as a control class. Data were collected with observation sheets and learning outcomes tests. The hypothesis is proved by a t-test. The results showed: (1) the high-level thinking skills of experimental class students are higher than the control class in terms of critical thinking skills, problem solving, and transfer of knowledge. (2) the learning outcomes of the experimental class students were higher than the control class shown by the results of the t test with a significance value (2-tailed) of 0.200 >significance value of 0.05. Thus, it can be concluded that the EXO OLO Task integrated Case Method model can improve high-level thinking skills and student learning outcomes so that it can become an alternative learning for teachers.